Isolation and chemistry of clerodane diterpenes from Dodonaea ceratocarpa - Moussa, Vassy; Skelton, B.; Payne, Alan (Pergamon-Elsevier Science Ltd, 2016)
A new clerodane was isolated from Dodonaea ceratocarpa and obtained in appreciable quantities (0.5% w/w plant). A variety of reactions on this clerodane provided access to a range of new derivatives, including cationic skeletal rearrangements and reduction reactions with lanthanide salt additives.